Intimate Partner Violence in Baja California’s Middle School Students. An Exploratory Study - Fernández de Juan, Teresa (Consorcio de Universidades Mexicanas A.C., 2023)
This article explores the degree, type, and differences by sex of intimate partner violence in students between 13 and 15 years old in Baja California (BC), Mexico. 5750 adolescents from public middle school in five municipalities participated. The prevailing types of violence (physical, sexual, and psychological), their causes, the cycle of violence, and abuse experienced and carried out (being a victim and/or victimizer) were inquired about. Without antecedents in BC, this study contributes to the early detection of situations that can be addressed and avoided with adequate programs. Psychological violence prevails through the need for control, lack of respect, and insults. Among its causes are jealousy, anger, and mistrust. Sexual violence followed due to the lack of respect about when and how to have sexual intercourse. Although few cases (22.73 %) admitted dating, 41.01% reported suffering or inflicting violence, with no relevant differences by sex.